How Difference Tasks Are Affected by Probability Format, Part 2: A Making Numbers Meaningful Systematic Review - Natalie C. Benda; Brian J. Zikmund-Fisher; Mohit M. Sharma; Stephen B. Johnson; Michelle Demetres; Diana Delgado; Jessica S. Ancker (MDM Policy & Practice)
Background. To evaluate the effect of data presentation format on communication of health probabilities, the Making Numbers Meaningful team undertook a systematic review. Purpose. This article presents evidence about difference tasks, in which a reader examines information to evaluate differences between probabilities, such as the effect of a therapy on the chance of recurrence. This article covers the effect of format on 5 outcomes: 1) perceptions of or feelings about effectiveness, 2) behavioral intentions or behaviors, 3) trust, 4) preference for the format, and 5) discrimination. Data Sources. MEDLINE, Embase, CINAHL, the Cochrane Library, PsycINFO, ERIC, ACM Digital Library; hand search. Finding Selection. Experimental/quasi-experimental studies comparing 2 or more formats for presenting quantitative health information. This article covers 205 findings from 101 unique studies reported in 84 articles. Data Extraction. Dual extraction of information on stimulus, task, and perceptual, affective, cognitive, and behavioral outcomes. Data Synthesis. Evidence is moderate to strong that behavioral intention is affected more by relative differences than absolute ones, by numerator-only graphics than part-to-whole graphics, by messages with anecdotes than without, and by information about what others chose. Evidence is strong that perceived and felt effectiveness is affected more by relative differences than by absolute ones and more by numerator-only graphics rather than part-to-whole graphics. For graphic preferences, bar charts were preferred to icon arrays and graphics with data labels to graphics without. Other comparisons had weak or insufficient evidence. Limitations. The detailed approach to evidence syntheses provides narrowly targeted evidence rather than broad statements. Conclusions. Moderate to strong evidence can be derived on effects of probability difference format on behavioral intention, perceived or felt effectiveness, and preference for format. Highlights Communicating relative risk differences as opposed to absolute risk differences, using numerator-only instead of part-to-whole graphics, and including anecdotes or information about others’ decisions will all increase intentions to engage in a behavior. Relative risks (rather than absolute risk differences) and numerator-only graphics (rather than part-to-whole) will also increase felt and perceived effectiveness. To illustrate probability differences, people tend to prefer bar charts over icon arrays and graphics with labels over those without. All findings regarding the impact of different presentation formats for probability differences on trust produced insufficient evidence.